Prevalence of Rotavirus among Children in Baghdad, Iraq, detected by molecular methods - Ali, Maryam Kareem; Shia, Jaafar Sataar (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Rotavirus, a leading cause of severe gastroenteritis in young children, has a significant global impact due to its high prevalence and potential for causing severe dehydration. Study design. This study was conducted to determine the prevalence of rotavirus among children under five years old in Baghdad, Iraq using molecular technique. Methods. Between November 2022 and August 2023, 120 stool specimens were collected from children exhibiting symptoms of diarrhea at a pediatric hospital. Rotavirus infection was assessed using immunochromatographic test and reverse transcriptase-polymerase chain reaction to detect and characterize the VP7 gene, a key marker of rotavirus infection. Results. It was observed that 97 out of 120 specimens tested positive for rotavirus, with immunochromatographic test detecting 110 cases (91.8%) and reverse transcriptase-polymerase chain reaction identifying 97 cases (80.8%) positive for the VP7 gene. The highest infection rates were observed in males (63.92%) and children aged 13-24 months (50.5%). Statistical analysis revealed an 80.8% overall prevalence of rotavirus among the study population. Conclusions. These findings underscore the significant burden of rotavirus infection in Baghdad and highlight the effectiveness of reverse transcriptase-polymerase chain reaction in detecting rotavirus strains. The results align with previous studies in Iraq, emphasizing the need for continued surveillance and vaccination efforts to control rotavirus-related diarrhea and reduce its impact on young children in the region.